Evolutionary Robotics: Model or Design? - Trianni, Vito (Frontiers in Robotics and AI, 2014)
In this paper, I review recent work in evolutionary robotics (ER), and discuss the perspectives and future directions of the field. First of all, I propose to draw a crisp distinction between studies that exploit ER as a design methodology on the one hand, and studies that instead use ER as a modelling tool to better understand phenomena observed in biology. Such distinction is not always that obvious in the literature, however. It is my conviction that ER would profit from the explicit commitment to the one or the other approach. Indeed, I believe that the constraints imposed by the specific approach would guide the experimental design and the analysis of the obtained results, therefore reducing arbitrary choices and promoting the adoption of principled methods that are common practice in the target domain, be it within the engineering or the life sciences. Additionally, this would improve the dissemination and the impact of ER studies on other disciplines, leading to the establishment of ER as a valid tool either for design or modelling purposes.